Antecedents of Transfer of Post-Harvest Handling Training among Small Scale Bean Grain Farmers in Uganda (Global Journal of Science Frontier Research, 2021)
Abstract not found
Keywords: training of transfer; transfer system factors; bean grain post-harvest training; uganda